Alain Badiou's 'Inaesthetics' and the melancholy novelist. Issue 4 (6th June 2016) - Brits, Baylee
Abstract : This article contrasts Alain Badiou's early work as a novelist with his later attempt to revolutionise and reorient aesthetics in line with his own philosophical system, a theory that would be published under the banner of 'inaesthetics'. This contrast hinges around a term that Badiou himself has used to distinguish these two projects: whilst Badiou understands himself as an affirmative philosopher, he sees himself by contrast as a melancholy novelist. Here, I show how this apparently minor statement in fact reflects not only on the relation between inaesthetics and Badiou's particular novelistic output but on the compatibility between inaesthetics and the novel as a genre. Here I analyse Badiou's first two novels, Almagestes (1964) and Portulans (1967), as exemplars of the capacity of the novel for internal, formal reflection within narrative. Or, in Badiouan terms, to exist as both a subject point in a truth procedure and enquire into its own capacity for the production of truth. The inaesthetic relation is constructed in opposition to a melancholic relation between philosophy and art and, by association, an understanding of melancholic artistic form. I will argue here that Badiou's inaesthetic solution to the problem of art and truth will remain inadequate so long as it rejects the melancholic form essential to the novel.